The terrestrial herpetofauna of Torres and Banks Groups (northern Vanuatu), with report of a new species for Vanuatu - Ineich, Ivan (Zootaxa, 2009)
A recent herpetological field trip to the Torres Group, an island group located at the northernmost border of Vanuatu, about 150 km from the southernmost Solomon Islands, allowed the collection of about 300 reptile specimens. Among these, Lepidodactylus guppyi is a new species record for Vanuatu. I also provide many new species records for the Torres Group, including two recently introduced species. The terrestrial herpetofauna of the islands of the Torres Group is reviewed for the first time and compared (1) to that of the Solomon Islands and particularly the southern Solomon island groups (Santa Cruz Group) bordering the Torres Group in the north, (2) to the remainder of Vanuatu and particularly Espiritu Santo Island which I recently surveyed, and (3) to a neighbouring group of islands in northern Vanuatu, the Banks Group. The Banks and Torres Groups share the same herpetofauna and their affinities are much stronger to the remainder of Vanuatu than to the southern Solomon Islands, thus suggesting their similar paleopositions during Melanesian arc movements.